A Comparison of Bone Mineral Density Measurements in Two Different Regions of Turkey - Ahmet İmerci; Nevres Hürriyet Aydoğan; Önder Yeniçeri (Galenos Yayinevi, 2017)
Objective: It was aimed to compare the values of bone mineral density (BMD) measurements made of patients in the osteoporosis (OP) unit in the provinces of Muğla and Erzurum provinces and to determine OP prevelance. Materials and Methods: The data were evaluated of a total of 3862 patients aged over 50 years, who were included in the study. Of patients; ages, sex, and body mass index (BMI) were recorded. Patients in Muğla were included in the 1st group, and patients in Erzurum were included in the second group. The BMDs of the spine (L1-4) and hip (femur neck) in both groups were measured using the dual energy X-ray absorptiometry (DEXA) method. Materials and Methods: The data were evaluated of a total of 3862 patients aged over 50 years, who were included in the study. Of patients; ages, sex, and body mass index (BMI) were recorded. Patients in Muğla were included in the 1st group, and patients in Erzurum were included in the second group. The BMDs of the spine (L1-4) and hip (femur neck) in both groups were measured using the dual energy X-ray absorptiometry (DEXA) method. Results: A total of 3862 patients were included in the study. In group 1, the total number of patients was 2611 and 2518 of them were female, 93 were male. In the group 2, 1251 patients were present and 1093 were female and 158 were male. The mean age was 63.63±8.84 years in group 1 and 65.44±9.26 years in group 2, and the difference was statistically significant (p<0.001). A statistically significant difference was determined between the groups in respect of BMI (p<0.001). A statistically significant difference was determined between the femoral neck T-scores of the cases (p<0.001). Between the females of the two groups, a statistically significant difference was determined in respect of the Lumbar 1-4 T-score but no difference was seen between the males (p<0.001, p=0.726, respectively). Conclusion: The femoral neck BMD values of patients in the Muğla region were found to be significantly lower than those of the patients in the Erzurum region. Despite the significant risk factors for BMD and OP in the Erzurum region of less sunlight and regional differences, the BMD values were determined to be higher. Nutritional habits are thought to be effective in the end. We believe that regional differences and local values are a factor to be considered in the interpretation of BMD.